The Effect of Changes in Flood Discharge on Sedimentation Rates in Middle Segment of Batang Kuranji Check Dam using HEC-RAS 6.0.0 - Zarinda, Septi Wila; Daoed, Darwizal; Nurhamidah, Nurhamidah (CIVED, 2024)
The magnitude of the longitudinal slope of river gratly determines the magnitude of sediment transport. This is due to the large flow velocity. This shape causes gradation of the river bed, especially upstream of the river. This phenomenon is seen in the middle segment of Batang Kuranji. where a sediment control buildg or check dam has been built. However, sediment transport and changes in river cross-section upstream still occur. Based on this phenomenon, a simulation of changes in flood discharge on sediment rate was carried out. This simulation was carried out using the Meyer Peter Muller method found in HEC-RAS 6.0.0. The simulation was carried out using 25 year planned flood discharge with smaller variations in discharge changes, namely Q1, Q2 and Q3. In general, the simulation results show that changes in flood discharge determine the magnitude of changes in sediment rates, the greater the flow discharge, the higher the sediment rate, both with and without check dams. The simulation results also show that the sediment rate in conditions with a check dam has decreased compared to conditions without a check dam, this shows that the presence of a check dam can reduce the sediment rate that occurred before the check dam was built.